Program Stimulus Budidaya Perikanan Terpadu Berbasis Agrosilvofisheries Plus dan Re-desain Kawasan Agrowisata Pendidikan (AgroEduTourism) Desa Sungai Bakau Besar Laut Mempawah Kalimantan Barat - Normagiat, Sigit; Didik, Didik; Nuraya, Tia; Fachria, Rizqy; Prasetyo, Riko; Ningsih, Sulistia; Wulan Sari, Dahlia; Murni Harfinda, Elliska; Meiratania, Marisa; Agung Iman, Sabda; Tohari, Tohari (LPPM Universitas Trunojoyo Madura, 2023)
The priority issues at Sungai Bakau Besar Laut (SBBL) village are about how to preserve the mangrove ecosystem in line with improving the community's economy. This is also the basis for the consideration of the PKMS Faperta UNU Kalimantan Barat in designing a mangrove ecosystem management program so that the area can have a tourist attraction, be more productive from a cultivation perspective and maintain its sustainability to support the community's economy. The aim of implementing this PKMS is as a stimulus for the people in SBBL village to play an active role in the conservation of mangrove ecosystems. In fact, it is hoped that through the AgroEduTourism design provided, it will be able to improve community welfare and contribute to accelerating mangrove rehabilitation to the surrounding area. Several solutions are offered to overcome the problems faced by partners, namely: 1) organizing training on integrated fisheries agribusiness management based on agrosilvofisheries, 2) Providing stimulus to aquaculture businesses in the form of providing fish seeds and providing starter feed. 3) Organize mangrove planting as a rehabilitation measure for degraded mangrove areas; 4) Redesigning tourist areas to make them more attractive and representative for the purpose of educational agro-tourism. The results of the PKMS carried out were the training of 15 SBBL residents to cultivate fish in an integrated manner. Provided assistance of 7500 fish breeds and feed to the training participants. The design of an agro-tourism area has been produced which has four functions, namely tourism, cultivation, education and conservation